The utilization of single-cell sequencing technology in investigating the immune microenvironment of ccRCC - Liu, Yuanxin; Wu, Guangzhen (Frontiers in Immunology, 2023)
The growth and advancement of ccRCC are strongly associated with the pr esence of immune infiltration and the tumor microenvironment, comprising tumor cells, immune cells, stromal cells, vascular cells, myeloid-derived cell s, and extracellular matrix (ECM). Nevertheless, as a result of the diverse a nd constantly evolving characteristics of the tumor microenvironment, prior advanced sequencing methods have frequently disregarded specific less pre valent cellular traits at varying intervals, thereby concealing their significanc e. The advancement and widespread use of single-cell sequencing technolo gy enable us to comprehend the source of individual tumor cells and the characteristics of a greater number of individual cells. This, in turn, minimiz es the impact of intercellular heterogeneity and temporal heterogeneity of the same cell on experimental outcomes. This review examines the attribut es of the tumor microenvironment in ccRCC and provides an overview of t he progress made in single-cell sequencing technology and its particular u ses in the current focus of immune infiltration in ccRCC.